Makna Tabarruj Perspektif Hadits dalam Kitab Syarah Shahih Muslim Karya Imam an-Nawawi (631-676 H.) - Vera Nur Azmi (Jurnal Penelitian Ilmu Ushuluddin, 2022)
This study has several objectives that is to find out how the understanding of the hadits about tabarruj, knowing how the quality of the hadith about tabarruj, and knowing the explanation of the hadith syarah about tabarruj contained in the book of Syarah Shahih Muslim by Imam an-Nawawi. The type of research used is qualitative research by applying library research. Then collect library sources, after that they are categorized according to research questions, then researchers collect data from library sources, namely the book of Syarah Shahih Muslim by Imam an-Nawawi, then carry out the takhrij al-hadith, naqd as-sanad and naqd al-matan. The results of the study explain that the meaning of tabarruj from the perspective of hadith is the actions of women who show their genitals, jewelry, and beauty of their bodies to those who are not mahram. After examining the quality of the hadith about tabarruj in Shahih Muslim, there are authentic and hasan. And for the quality of the hadith  there is nothing that contradicts the Qur’an. To conclude the meaning of tabarruj in Syarah Shahih Muslim is focused on the meaning of two hadiths, namely the hadith about women who dress but their genitals are visible and the prohibition of connecting hair for woman.